PEMANFAATAN MODENG BAGE (BIJI ASAM) SEBAGAI MEDIA PEMBELAJARAN PADA MATERI MONOHIBRID UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA XII A 1 SMA NEGERI 1 LAPE - Muhammad Nur (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT: This study aims to increase biology students' motivation to learn the grade XII IPA 1SMA Negeri 1 Lape academic year 2014/2015 with the utilization of modeng bage (acid seed) as a learning medium on monohibrid material. While the benefits to be obtained as follows: (1) For educators; in learning and learning can take advantage of the environment, the components around the school, home, the environment where the most important is still relevant to the material or in accordance with basic competencies, (2) for students; so that the students can take advantage of the space (space), time and any media and able to adjust to the methods, approaches in teaching and learning activities, (3) for institutions (schools), schools obtain information and simultaneously provide stimulus so that students can later be useful for nation, state, religion, family and society. Learning media referred to in this article is in the form of modeng bage (acid seed) as a medium on learning, while the learning motivation is the interest of student learning. The research type was PTK, the result of data analysis showed that modeng bage as contextual learning medium on monohybrid material in obtaining students' responses above the success standard (55% First Stage) and (70% Second Stage). Table 5 shows that 53.15%> 37.50% of this data explains that teaching using a particular medium has an effect on student motivation, although it is still below the minimum standard set at 55%, (53.15% <55%). After we analyzed the data in Table 6, the students' responses were found that using modeng bage as a learning medium had a significant effect that was 84.38%> 75% or above the success rate of 84.38%> 70%. Likewise with the various interviews we did that students, teachers gave positive responses and there were also negative responses. But in general give a positive response to the media we use. So it can be said that there is a significant influence on the utilization of modeng bage as a medium of learning on the motivation of students studying XIIA class 1 odd semester.